2020
DOI: 10.1038/s41419-020-2507-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel function of IMPA2, plays a tumor-promoting role in cervical cancer

Abstract: Discovery of genes and molecular mechanism involved in cervical cancer development would promote the prevention and treatment. By comparing gene expression profiles of cervical carcinoma in situ (CCIS) and adjacent normal tissues, we identified a potential cancer-promoting gene, IMPA2. This study aimed to elucidate the role of IMPA2 and underlying molecular mechanisms in cervical cancer progression. To do this expression of IMPA2 was compared between human cervical cancer and corresponding adjacent normal cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…Thus, the development of new molecules for cervical cancer screening and treatment is urgently needed. In this study, IMPA2 was a novel gene we previously found from transcriptomics results that has been proved to be a potential tumor-promoting gene (11). And we further con rmed that IMPA2 may affect cancer cell death through inducing cell apoptosis.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Thus, the development of new molecules for cervical cancer screening and treatment is urgently needed. In this study, IMPA2 was a novel gene we previously found from transcriptomics results that has been proved to be a potential tumor-promoting gene (11). And we further con rmed that IMPA2 may affect cancer cell death through inducing cell apoptosis.…”
Section: Discussionsupporting
confidence: 69%
“…Our previous study rstly showed that IMPA2 may promote the progression of cervical cancer (11). In this study, we further revealed that silenced-IMPA2 could aggravate apoptosis regulated by activating the p53signaling pathway through upregulating the expression of AIFM2, suggesting a potential therapeutic target to cervical cancer treatment.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Further examination of the individual genes within the signature revealed upregulation of chromatin regulation and DNA repair genes CDT1, NCAPD3 and EXO1. The top gene in this signature, IMPA2, has recently been reported to drive cervical cancer progression with a potential novel role in DNA repair 35 .…”
Section: Targetable Pathways Within Pnsting Low Poor Prognosis Tumorsmentioning
confidence: 99%